2020
DOI: 10.3389/fphar.2020.582625
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the Plasma Concentration of Eltrombopag With Efficacy in the Treatment of Refractory Aplastic Anemia: A Single-Centre Study in China

Abstract: Background and purpose: Eltrombopag (ELT) can be effective in the treatment of relapse/refractory aplastic anemia (AA) patients. Responses and adverse drug reactions (ADRs) differed greatly among individuals treated at the same dosage of ELT.Methods: Patients diagnosed with nonsevere aplastic anemia (NSAA) between January 2018 and January 2019 in Peking Union Medical Colleague Hospital who were refractory to immunosuppressive therapy were treated with ELT and followed up for at least 6 months. Plasma concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Some studies indicate that insufficient concentration may impact the efficacy of eltrombopag. Zuo et al 15 discovered that the risk of eltrombopag inefficacy in aplastic anemia at a concentration between 11.2 and 15.2 µg/ml was 0.028-fold (P = 0.041) of that at a concentration between 3.2 and 7.2 µg/ml in a prospective and longitudinal cohort study. Dionisi et al 16 found that patients presenting a complete response showed augmented eltrombopag exposure parameters compared to subjects with partial or no response in ITP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies indicate that insufficient concentration may impact the efficacy of eltrombopag. Zuo et al 15 discovered that the risk of eltrombopag inefficacy in aplastic anemia at a concentration between 11.2 and 15.2 µg/ml was 0.028-fold (P = 0.041) of that at a concentration between 3.2 and 7.2 µg/ml in a prospective and longitudinal cohort study. Dionisi et al 16 found that patients presenting a complete response showed augmented eltrombopag exposure parameters compared to subjects with partial or no response in ITP.…”
Section: Discussionmentioning
confidence: 99%
“…13 Another case was reported of a 57-year-old female from China with chronic ITP who developed reversible hyperpigmentation after several months of treatment with eltrombopag . 14 In addition, Zuo et al 15 found that an elevated risk of ADRs might be correlated with eltrombopag concentration. Furthermore, the plasma concentration of eltrombopag, which may be affected by gender, age, race, concomitant drugs, and other factors, has a great individual variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute liver failure induced by eltrombopag may be caused by an impaired elimination of the drug due to genetic variants involved in the major pharmacokinetic pathways, leading to the high plasma eltrombopag accumulation in the body. Further research is needed to investigate the proper dose of eltrombopag in Chinese populations and different age groups and the relationships between the plasma concentration or pharmacogenetic of eltrombopag and its safety and efficacy (16).…”
Section: Discussionmentioning
confidence: 99%